Multivariate geochemical and mineral patterns in the Precambrian basement of western Canada - Burwash, R. A.; Culbert, R. R. (Canadian Journal of Earth Sciences, 1976)
R-mode factor analysis, discrimant analysis, trend surface, and canonical trend surface analyses are applied to the 42 variables measured for 171 Precambrian igneous and high grade metamorphic rocks, sampled in deep drill holes in the western Canada sedimentary basin. Low-grade metasedimentary rocks and post-Hudsonian diabase intrusives are excluded. The four strongest R-mode factors are related to processes of regional metamorphism. These are: potassium metasomatism, shearing with the development of secondary foliation, chloritization, and mylonization. Potassium metasomatism appears mainly to be later than the three other processes.Regional lineaments in the western Shield, identified from tectonic, gravity, and magnetic maps, when combined with trend surface maps from drill hole data, suggest southwestward extensions of major lithologic tectonic units of the Churchill province. The fivefold division of the subsurface Precambrian includes, from north lo south: I—Liard block (Slave and Bear provinces, in part), II—Athabasca mobile belt (restricted). III—Cree Lake – Calgary belt, IV—Kisseynew–Sweetgrass belt, and V—Superior province (Assiniboia block, restricted).The two major Phanerozoic crustal flexures in the Western Canada basin, the Peace River arch and the Williston basin, correspond to canonical trend surface highs and lows, respectively. Their persistent isostatic tendencies are linked to differing Hudsonian metamorphic histories.A depletion of trace metal content, which accompanies shearing, can be traced diagonally across northern Alberta. The southwestward projection of this belt matches the portion of the Canadian Cordillera barren of major ore deposits.